1989
DOI: 10.1073/pnas.86.2.735
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mRNA splicing generates multiple forms of peptidyl-glycine alpha-amidating monooxygenase in rat atrium.

Abstract: Peptidyl-glycine a-amidating monooxygenase (PAM; EC 1.14.17.3) catalyzes the conversion of a variety of glycine-extended peptides into biologically active aamidated product peptides in a reaction dependent on copper, ascorbate, and molecular oxygen. We have isolated and sequenced cDNAs representing the two major classes of PAM mRNA in the adult rat heart atrium. The two types of cDNA, rPAM-1 and rPAM-2, are identical except for the deletion of a 315-base-pair segment within the protein coding region in rPAM-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 29 publications
(29 reference statements)
1
66
0
Order By: Relevance
“…Whereas in the stomach most of the gastrin cells were immunoreactive for PAL and only some were positive for PHM, in the colon only immunoreactivity for PHM was found (Martinez et al, 1993b). Tissue specific expression of alternate mRNA splice forms and post-translational proteolysis and secretion of PAM proteins have been extensively studied (Oyarce and Eipper, 1993;Stoffers et al, 1989) and could explain some of the differences found. In addition, possible differences in sensitivity between the antibodies could also explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in the stomach most of the gastrin cells were immunoreactive for PAL and only some were positive for PHM, in the colon only immunoreactivity for PHM was found (Martinez et al, 1993b). Tissue specific expression of alternate mRNA splice forms and post-translational proteolysis and secretion of PAM proteins have been extensively studied (Oyarce and Eipper, 1993;Stoffers et al, 1989) and could explain some of the differences found. In addition, possible differences in sensitivity between the antibodies could also explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification by PCR was performed using standard Taq buffer (Promega) with the addition of 10% glycerol (30 cycles, denaturation 95°C, 1 min; annealing 50°C, 1 min; extension 72°C, 2 min). The primers for PCR were designed from the published sequence for rat atrial PAM (Stoffers, Green & Eipper, 1989) and corresponded to regions spanning the following functional domains of PAM: the peptidylglycine ĂĄ_hydroxylating mono-oxygenase (PHM) domain (nucleotides 482-500 and 1012-1030, primers 1 and 2, respectively), the protease-sensitive domain (nucleotides 1490-1508 and 1770-1788, primers 4 and 5, respectively) and the transmembrane domain (nucleotides 2760-2778 and 3173-3192, primers 6 and 7, respectively). In addition, different species of PAM were distinguished using primer 7 and a primer (3) to nucleotides 1454-1473.…”
Section: Identification Of Pam Transcriptsmentioning
confidence: 99%
“…This could be explained if PAM molecules present in A-and B-cells were somehow different, so that each form could only be recognized by one of the antisera but not by the other. Such molecular differences between mouse A-and B-cell's PAM molecules could be due either to different posttranslational processing (e.g., proteolysis, glycosylation, phosphorylation), giving rise to conformational changes of the protein, or to alternative splicing, as previously reported in pancreatic carcinoma cells (Tateishi et al 1994) and in other tissues (Stoffers et al 1989(Stoffers et al ,1991Zhang et al 1997).…”
Section: Diversity Of Pam Enzymes In Mouse Endocrine Pancreatic Cell mentioning
confidence: 94%